Analisis Pengaruh Kreativitas Iklan dan Endorser Terhadap Keputusan Pembelian Online di E-commerce Shopee - Sofiana; Febrina Hambalah (Journal Of Accounting and Business, 2022)
The problems in online purchasing decisions those are made by someone on Shopee e-commerce can be influenced by the advertising creativity and the use of endorsers or the celebrity influencers are as promotional strategies. For this reason, Shopee e-commerce must have creative advertising concepts and choose the right endorser to be able to attract the consumers make online purchases on Shopee e-commerce, it is especially for millennials who are considered the people who make the most purchases online. This study aims to describe how the influence of Advertising Creativity and Shopee Endorser on Online Purchase Decisions in E-commerce on Business Administration Students, Hang Tuah University of Surabaya. The research method that is used in this study, it is quantitative with the data analysis that is used in the form of statistics/quantitative or numbers. The results showed In accordance with the results of the calculation of the variable regression coefficient, the constants of each Advertising Creativity (X1) and Endorser (X2) variables show a positive value, thus there is a unidirectional effect between these variables and Purchase Decisions (Y) on Shopee e-commerce. In accordance with the results of the multiple correlation test (R) shows the result that is 0.842 and guided by the correlation coefficient 0.90-1000 = very strong, thus it can be concluded that there is a very strong relationship between Advertising Creativity (X1) and Endorser (X2) variables on Purchase Decisions (Y) on Shopee e-commerce. The results of the t-test and f-test together show that the results of each variable simultaneously and partially have a positive and significant effect on Purchase Decision (Y) on Shopee e-commerce